Cost Structure and Information Asymmetry Analysis in the Sugarcane Cultivation Supply Chain in Jember Regency, East Java - Suwandari, Anik; Aji, Joni Murti Mulyo; Kuntadi, Ebban Bagus; Rondhi, Mohammad; Rokhani, Rokhani; Yanuarti, Rizky (SOCA: Jurnal Sosial Ekonomi Pertanian, 2025)
Sugarcane farmers face the persistent issue of information asymmetry, an imbalance of knowledge between farmers and sugar mills that disrupts transparency and undermines trust within the supply chain. In addition, a high dependency on intermediaries and limited access to financing further exacerbates the economic disparity experienced by farmers. Investigating cost structures, information asymmetry, and partnership models within the sugarcane supply chain is therefore essential. This study was conducted in 2024 in Jember Regency, East Java. The methods employed include cost structure analysis, identification of information asymmetry, and estimation of sugar mill production potential. The findings reveal that sugarcane cultivation in Jember is predominantly organized under two partnership schemes: the Revenue-Sharing System (Sistem Bagi Hasil/SBH) and the Sugarcane Purchase System (Sistem Pembelian Tebu/SPT). Information asymmetry remains a major challenge, as farmers heavily rely on sugar mills as their primary source of information (78.4%), thereby diminishing their bargaining power. Despite being financially profitable (with an average income of IDR 24.4 million per hectare), the cost structure is largely concentrated in labor (59.24%) and fertilizers (20.56%). Market transaction costs account for 87.1% of total expenditures, indicating significant inefficiencies within the supply chain. An analysis of sugar mill capacity shows considerable variation in production scale; however, sugarcane supply remains unstable as farmers tend to sell to mills offering higher prices. Strengthening farmer groups, improving market information transparency, implementing integrated planting coordination, and fostering more equitable partnership models are all critical measures to ensure supply chain stability and enhance farmer welfare.